2021
DOI: 10.20469/ijbas.7.10003-1
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Impact of Cash Management on the Financial Performance of the Listed Manufacturing Companies from Muscat Securities Market, Sultanate of Oman

Abstract: Cash is a valuable yet scarce resource that all businesses have in limited quantity. Present research on cash management has focused on its connection with many important areas such as the effect on the liquidity of the business, its financial performance, bankruptcy, and the overall working capital itself. To validate the relationships between cash management and financial performance, 36 companies listed in Muscat Securities Market (MSM) had been chosen over time, starting from 2014 ending to 2019. For this,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
2
1
0
Order By: Relevance
“…A p-value of 0.046 was attained which was below 0.05 significance level hence the null hypothesis was rejected and the study found that cash management significantly impacted the financial performance of businesses. This findings align with Chintha and Prasad (2020)…”
supporting
confidence: 87%
See 1 more Smart Citation
“…A p-value of 0.046 was attained which was below 0.05 significance level hence the null hypothesis was rejected and the study found that cash management significantly impacted the financial performance of businesses. This findings align with Chintha and Prasad (2020)…”
supporting
confidence: 87%
“…The companies whose data were collected for the study were all found to have recorded improved financial performances as a result of improvement in their WCM strategies. Chintha and Prasad (2020) supported the findings of Abdikani et al (2018), emphasized that although firms had different approaches in managing their working capital, an objective management practice ultimately improved financial performance. Closer home, Mlambo (2018) investigated how effective debt management practices were in terms of improving the performance of a DHL International (Zimbabwe), and the study found that factoring debts promptly, timely payment plans, follow up as well as rotational debt collection practices improved debt collection in the organization.…”
Section: Journalsupporting
confidence: 58%
“…Given that cash is a valuable resource, any firm must manage it properly and efficiently, which is often done using the method of cash management. According to Sam Sundar Chintha, the definition of cash management is "the management of a firm's cash and cash equivalents to ensure that there is sufficient cash available to support operations, finance investments, and satisfy all other financial obligations [6].…”
Section: Introductionmentioning
confidence: 99%